P81 Pre-transplant histological assessment in patients with alcoholic liver disease does not predict risk of recidivism post liver transplantation. (6th September 2011) - Prentis, J; McPherson, S; Burt, A; Manas, D; Snowden, C; Hudson, M; Masson, S
Abstract : Introduction: Liver transplantation for alcoholic liver disease (ALD) is well established, but it remains a controversial indication. Assessment of patients in whom alcohol has been a contributing factor to chronic liver disease aims to identify those at risk of relapse. As well as psychological assessment, histological evidence of steatohepatitis may indicate ongoing alcohol consumption. Aim: To determine the prevalence of histological evidence of ongoing alcohol use among patients undergoing liver transplant assessment for ALD and its affect on listing and risk of recidivism. Method: Consecutive patients with ALD assessed for liver transplantation between 2006 and 2010 were included. Transjugular liver biopsy was performed routinely in all patients and specimens were reviewed by an expert hepatopathologist. Outcomes including decision to list for transplant, survival and recidivism (patient admission or blood alcohol detection) were recorded Results: 122 patients were included (70% male, median age 55) with diagnoses of lone ALD (92), ALD/HCV (10) and HCC (10). Histology was insufficient for analysis in four. Most patients (108, 89%) had histological evidence of micronodular cirrhosis without evidence of steatosis or steatohepatitis, suggesting abstinence. Of these, 52 were listed for transplantation though two were subsequently removed for recidivism. To date, 39 have been transplanted; 1-year follow-up was available in 28. The overall 1-year survival was 90% and 28% had returned to drinking alcohol (n=7), although none were 'problem' drinkers. In the remaining 10 patients, histology revealed cirrhosis with active steatohepatitis (n=2), chronic viral hepatitis (n=1) and mild steatosis (n=7). One patient with steatohepatitis was known to be drinking at the time of assessment; the remainder were listed for transplant. Subsequently, one patient with steatosis was found to be drinking and removed. To date, six have been transplanted and survived to 1 year, with two returning to alcohol post-transplant. Conclusion: Histological analysis during liver transplant assessment does not determine the decision to list for liver transplantation nor predict the risk of recidivism. As a result, we no longer routinely perform liver biopsy during liver transplant assessment. A significant proportion of patients return to alcohol consumption post liver transplantation.